The institutional design of CUSMA: Improvement or reversal vis-à-vis NAFTA? - Ortiz Mena L. N., Antonio; Schiavon, Jorge (Revue québécoise de droit international / Quebec Journal of International Law / Revista quebequense de derecho internacional)

(untitled) (Société québécoise de droit international, 2022)
In this article we comparatively analyze the institutional design of the 2020 Canada-United States-Mexico Agreement (CUSMA) vis-à-vis the 1994 North American Free Trade Agreement (NAFTA). In the modernization of NAFTA into CUSMA, three strategies were employed: updating, upgrading, and adjusting the institutional design. We explore whether the implementation of these strategies provide a better governance of free trade and investment in the region compared to NAFTA. To do so, we conduct an in-depth evaluation of both agreements. Our central argument is that there were both progress and reversals in several areas: for example, the strength and powers of dispute settlement mechanisms, an improvement in the implementation of the working groups, changes in the flexibility or rigidity of its architecture depending on the sector analyzed, among many others. The article is comprised of three sections, each of them dealing with one of the three strategies under scrutiny. Finally, based on the central findings, we provide some public policy recommendations to strengthen the governance of free trade and investment in North America through the CUSMA.